2021
DOI: 10.3390/pathogens10091149
|View full text |Cite
|
Sign up to set email alerts
|

Updated Evidence on the Epidemiology of Hepatitis C Virus in Hemodialysis

Abstract: Prevalence rates of HCV infection are decreasing in hemodialysis units of most developed countries; however, nosocomial transmission of HCV continues to occur in the hemodialysis setting, not only in the emerging world. According to the Dialysis Outcomes and Practice Patterns Study (DOPPS, 2012–2015), the prevalence of HCV among patients on regular hemodialysis was 9.9%; in incident patients, the frequency of HCV was approximately 5%. Outbreaks of HCV have been investigated by epidemiologic and phylogenetic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, with the availability of DAA, the approach does not stand to reason. Furthermore, isolation of HCV viremic patients has not been firmly confirmed as an effective measure to prevent HCV spread, but in certain circumstances, for example, low patient:personnel ratio, it may be justified [ 9 , 24 , 25 ]. Epidemiological investigations have shown that patients dialyzed nearby are at a greater risk of HCV infection than those dialyzed on the same machine as HCV viremic ones [ 9 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the availability of DAA, the approach does not stand to reason. Furthermore, isolation of HCV viremic patients has not been firmly confirmed as an effective measure to prevent HCV spread, but in certain circumstances, for example, low patient:personnel ratio, it may be justified [ 9 , 24 , 25 ]. Epidemiological investigations have shown that patients dialyzed nearby are at a greater risk of HCV infection than those dialyzed on the same machine as HCV viremic ones [ 9 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, isolation of HCV viremic patients has not been firmly confirmed as an effective measure to prevent HCV spread, but in certain circumstances, for example, low patient:personnel ratio, it may be justified [ 9 , 24 , 25 ]. Epidemiological investigations have shown that patients dialyzed nearby are at a greater risk of HCV infection than those dialyzed on the same machine as HCV viremic ones [ 9 , 14 ]. This may imply that non-adherence to mandatory precautions and not the machine itself is an obstacle to eradicating CHC; this factor requires due consideration rather than mere isolation of patients with CHC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Karkar et al, 2006 ) The furthermost recurrent viral infections faced in hemodialysis units due to HBV, HCV and, to a smaller degree, HIV. ( Bernieh, 2015 , Fabrizi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis, a commonly used extra-renal purification technique, allows prolonged survival of patients with chronic renal failure who have reached the end stage. However, it induces many complications, mainly infectious, including viral hepatitis B and C [36,37].…”
Section: Discussionmentioning
confidence: 99%